An herbal formulation "Shenshuaifu Granule" alleviates cisplatin-induced nephrotoxicity by suppressing inflammation and apoptosis through inhibition of the TLR4/MyD88/NF-κB pathway. (24th April 2023) - Jin, Xiaoming; He, Riming; Liu, Jiahui; Wang, Yuzhi; Li, Zhongtang; Jiang, Beibei; Lu, Jiandong; Yang, Shudong
Abstract: Ethnopharmacological relevance: Shenshuaifu Granule (SSF) is an in-hospital preparation approved by the Guangdong Food and Drug Administration of China. It has been clinically used against kidney diseases for more than 20 years with a definite curative effect. Aim of the study: Cisplatin (CDDP) is a first-line chemotherapeutic drug in clinical practice, primarily excreted by the kidney with nephrotoxicity as a common side effect. Approximately 5-20% of cancer patients develop acute kidney injury (AKI) after chemotherapy; however, prevention and control strategies are currently unavailable. Therefore, it is important to identify safe and effective drugs that can prevent the nephrotoxicity of CDDP. SSF is an herbal formulation with 8 herbs, and has been used to protect the kidney in China. Nonetheless, its mechanism in relieving CDDP nephrotoxicity remains unclear. Therefore, this work attempt to prove that SSF can alleviate CDDP nephrotoxicity. We also explore its mechanism. Materials and methods: First, Thin Layer Chromatography (TLC) of a few herbs in SSF were performed for quality control. Several open-access databases were used to identify the active ingredients of SSF, their corresponding targets, and CDDP-induced nephrotoxicity targets. We performed Protein-Protein Interaction (PPI), Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. Next, the results of network pharmacology were validated using CDDP-induced nephrotoxicity mouse models. Renal function in the mice was assessed by analyzing the levels of serum creatinine (Scr) and blood urea nitrogen (BUN). On the other hand, renal damage was assessed by determining the level of tubular injury and apoptotic cells using Periodic acid-Schiff (PAS) staining and Terminal Dutp Nick End-Labeling (TUNEL) staining, respectively. The expression of inflammatory and apoptotic-related targets including IL-1β, IL-6, TNF-α, Cox-2, Bax, Bcl-2, Cleaved-caspase 3, and Cleaved-caspase 9 was determined using Western Blot (WB) and Immunohistochemistry (IHC). Furthermore, WB was used to analyze the expression of proteins associated with the TLR4/MyD88/NF-κB pathway in the kidneys of mice with CDDP-induced nephrotoxicity. Finally, molecular docking simulations were performed to evaluate the binding abilities between major active ingredients of SSF and core targets. Result: Through network pharmacology, we identified 127 active ingredients of SSF and their corresponding 134 targets. Additional screening identified 14 active ingredients and 17 targets for further analysis. In biological process (BP), the targets were enriched in inflammation and apoptosis, among others. In KEGG terms, they were enriched in apoptosis and NF-κB pathways. Animal experiments revealed that SSF significantly reduced the levels of Scr and BUN and prevented renal tubular damage in mice treated with CDDP. In addition, SSF inhibited inflammation and apoptosis by targeting the TLR4/MyD88/NF-κB pathway. Molecular docking revealed good binding capacities of active ingredients and core targets. Conclusion: In summary, the experimental findings were consistent with the network pharmacological predictions. SSF can inhibit inflammation and apoptosis by targeting the TLR4/MyD88/NF-κB pathway. Taken together, our data suggest that SSF is an alternative agent for the treatment of CDDP-induced nephrotoxicity. Graphical abstract: Image 1